Problematika Perempuan Karier dalam Film Hanum dan Rangga: Faith and The City Analisis Semiotika Roland Barthes - Fikriyatul Islami Mujahidah (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, State Islamic University Sunan Kalijaga Yogyakarta, 2021)
Grassy and career might be a common choice for women today. Unfortunately, the clasp of patriarchate culture seemed to slip away. Where women who have a career still have to face various types of problems. The study analyses the problems that career women face with research subjects of Hanum and Rangga: Faith and The City. The method of analysis used is Roland Barthes semiotics with a qualitative descriptive approach. Data obtained is analyzed to identify the meanings of denrotations, connotations, and myths. It is found to be problematic that women must face in external and internal factors. Among other things; Cultural constructions of patriarchate, employment opportunities, and homemaking. Internal factors; Parenting and uncertainty.